PENGARUH VARIASI PERSENTASE ABU SEKAM PADI (ASP) DAN ABU CANGKANG LOKAN(ACL) SEBAGAI PENGGANTI SEBAGIAN AGREGAT HALUS DAN SEMEN TERHADAP KUAT TEKAN MORTAR (Kajian Terhadap Adukan Mortar 1Pc : 3Ps) - Junita Eka Susanti; Ade Sri Wahyuni; Elhusna Elhusna (Universitas Bengkulu, 2019)
The purpose of this research is to know the influence of sea shell ash (SSA) and rice husk ash (RHA) as partial replacement of cement and sand toward the strength of mortar. The mold with dimension 50 mm x 50 mm x 50 mm were used to cast the mortar.There are 16 variation made from different percentages of RHA and SSA used.The range initial flow used was 80-100%. The result shows that the normal mortar has the highest strength of all. The decrease of mortar strength with RHA and SSA was in the range of 11.60%-59.11% in comparison with normal mortar.